The effect of a proposed program of modified Tae Bo exercises on the level of some physical fitness, physiological and skillful elements of basketball players - Mohamed Ramadan Abd Rabbo, A.; Abdullah El-Ruby, A. (World Journal of Sport Sciences, 2010)
The research aimed to design a proposed training program of modified Tae Bo exercises to be performed in the motor course of the skillful performance of basketball players using the music. That is to introduce an element of fun and excitement during the performance, which goes beyond the traditional methods of training that give rise to boredom and fatigue. Studies dealt with Tae Bo exercises have shown their contribution to the development of physical elements such as strength, flexibility, agility, speed and endurance in addition to the physiological efficiency and increase of oxygen consumption. This prompted both researchers to address this research study in an attempt to identify the effect of modified Tae Bo exercises on some physical fitness, physiological and skillful elements of basketball players. The researchers used the experimental method with the experimental design for two groups, one experimental and the other control of 10 players each. The researchers applied the basic experiment for 12 weeks by three training units a week. The results showed that the modified Tae Bo exercises had a positive effect on the special elements of physical fitness and physiological and skillful variables under discussion.